Produção de metano a partir de codigestão anaeróbia de vinhoto e glicerol residuais - Steffens, Fabricio Hoeltz (My University, 2017)
Taking into account the economic importance that the sugar-alcohol industry and biodiesel represent for Brazil, as well as the country's leading position in this world economic scenario, adequate management of the effluent generated by the industries becomes fundamental. In order to minimize the associated environmental impacts, given that one liter of ethanol produced generates up to fifteen liters of vinasse and that each ton of biodiesel generates one hundred kilos of glycerol, available technologies can be used, as in the case of anaerobic processes. This study evaluated twelve experiments in anaerobic process in laboratory scale using effluent of vinasse and glycerol post treatment by acidogenesis process, coming from the sugar-alcohol industry and biodiesel. Methane production parameters were determined, among other aspects. The three reactors of the four experiments that presented the most significant results in terms of methane production in the monitored time period, using only residual vinasse, were V4.3, V2.3 and V3.3, in volumes of 6,241 mL, 6,087 mL and 4,845 mL, respectively. In the experiments using also glycerol, the results presented maximum methane yields of 8,687 mL, 7,990 mL and 6,640 mL, for vinasse and glycerol ratios of 80/20, 60/40 and 20/80, respectively.
Levando-se em consideração a importância econômica que a indústria sucroalcooleira e do biodiesel representam para o Brasil, bem como a posição de destaque do país neste cenário econômico mundial, uma gestão adequada do efluente gerado pelas indústrias torna-se fundamental. A fim de minimizar os impactos ambientais associados, tendo em vista que um litro de etanol produzido gera até quinze litros de vinhoto e que cada tonelada de biodiesel gera cem quilos de glicerol, tecnologias disponíveis podem ser utilizadas, como no caso de processos anaeróbios. Este estudo avaliou doze experimentos em processo anaeróbio em escala laboratorial utilizando efluente de vinhoto e glicerol pós tratamento por processo de acidogênese, oriundo da indústria sucroalcooleira e do biodiesel. Foram determinados parâmetros de produção de metano, entre outros aspectos. Os três reatores dos quatro experimentos que apresentaram resultados mais significativos em termos de produção de metano no período de tempo monitorado, utilizando somente vinhoto residual, foram o V4.3, V2.3 e o V3.3, em volumes de 6.241 mL, 6.087 mL e 4.845 mL, respectivamente. Já nos experimentos utilizando também glicerol, os resultados apresentaram produções máximas de metano de 8.687 mL, 7.990 mL e 6.640 mL, para relações de proporções de vinhoto e glicerol de 80/20, 60/40 e 20/80, respectivamente.
Keywords: Digestão anaeróbia; Resíduos industriais; Metano; Biorreatores; Anaerobic; Factory and trade waste; Bioreactors; Methane